The Effect of Discovery Learning Method Towards Students’ Reading Comprehension on Analytical Exposition Text in SMA N 1 Payung Sekaki - Shinta Liberta; Irwandi Irwandi; Eliza Eliza; Merry Prima Dewi (Pusdikra-Publishing.com, 2024)
This research was aimed at finding out the effect of using discovery learning method toward student’s reading comprehension on analytical exposition text in SMA N 1 Payung Sekaki. The rationality of this research was based on the student’s problems in reading comprehension when learning English. First, Students have difficulties in comprehending analytical exposition text. Second, students do not understand the material analytical exposition text. Third, students have lack of motivation in learning This research employed quantitative method. In this research, the researcher used quasi-experimental research design by comparing two classes. The sample of this research was the 11th grade students at SMA 1 Payung Sekaki. The research instrument of this research was reading test, which were tested for pre-test and post-test. The data was analyzed by using SPSS 22. The result of the research indicated that there was significant effect of students reading comprehension between the students who were taught by using discovery learning method and without using discovery learning method. It can be seen from the calculation of the data in one sample t test and paired sample t-test it showed the significance of 2-Tailed was 0,000 < 0,05 so that Ha was accepted and Ho was rejected. It can be concluded, there is significant effect of using discovery learning method.